MONGOLIA’S INVASION OF THE KHOREZMSHOHS - Yakubova Dilorom Tadjiyevna; Boborahimov Shohruh Innoyatillo Oglu (International Journal Of History And Political Sciences, 2023)
In the history of Uzbek statehood The Khorezmshahs, who were of great importance, were a state with great borders. Under such conditions, in the early 13th century, Genghis Khan united the Mongols in a single state on the territory of present day Mongolia. The territories of the two great kingdoms remained adjacent, and so he wanted to expand his territory even further. Gengis Khan and Khorezmshah Alouddin Muhammad began to prepare for battle againts each other. This article discusses the relations of Genghis Khan and the Mongols with the Khorezmshah state, their attacks and their consequences.